Risk prediction model for waitlist mortality in patients with left ventricular assist devices - Anjan Tibrewala, MD, MS; Duc Thinh Pham, MD; Mo Hu, MS; Lucia C. Petito, PhD; Jonathan D. Rich, MD; Finn Gustafsson, MD, PhD; Theo M.M.H. de By, MBA, PhD; Kevin Veen, MD, PhD; Donald M. Lloyd-Jones, MD, ScM; Sanjiv J. Shah, MD (JHLT Open)
Background: Left ventricular assist devices (LVAD) are a bridge to heart transplantation (HT). Given limited donor organs, assessment of risk of waitlist mortality is important for waitlist prioritization for HT. We sought to derive and validate a risk prediction model for waitlist mortality in LVAD patients. Methods: Adult patients with a continuous-flow, centrifugal, durable LVAD listed or likely to be listed for HT in the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) were included. The outcome was time to all-cause mortality within 2 years from implant. We considered 41 candidate predictors at 3 months post-implant. Univariate Fine-Gray models and 4 logistic regression techniques (logistic, LASSO, random forest, gradient boosting) were used to select variables for a final survival model using the Fine-Gray method. The model was validated in INTERMACS and in an independent cohort (European Registry for Patients with Mechanical Circulatory Support [EUROMACS]). Model discrimination and calibration were evaluated. Results: The INTERMACS cohort included 2364 patients with 268 (11%) deaths. A risk prediction model for waitlist mortality at 2 years was derived with area-under-the-curve (AUC) of 0.72 (95% CI 0.67–0.77). The EUROMACS cohort included 577 patients with 70 (12%) deaths. The model AUC was 0.62 (95% CI 0.55–0.70). The model predicted waitlist mortality when divided into low-, medium-, or high-risk groups in the INTERMACS (p<0.001) and EUROMACS (p=0.0099) cohorts. Conclusions: We derived and validated a risk prediction model for waitlist mortality in LVAD patients using 2 independent cohorts. Our risk assessment model can inform HT prioritization in LVAD patents.